2017
DOI: 10.1007/s10439-017-1881-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Hand Motor Symptoms in Parkinson’s Disease: A Proof-of-Principle Study Using Inertial and Force Sensors

Abstract: This proof-of-principle study describes the methodology and explores and demonstrates the applicability of a system, existing of miniature inertial sensors on the hand and a separate force sensor, to objectively quantify hand motor symptoms in patients with Parkinson’s disease (PD) in a clinical setting (off- and on-medication condition). Four PD patients were measured in off- and on- dopaminergic medication condition. Finger tapping, rapid hand opening/closing, hand pro/supination, tremor during rest, mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…One of the sensors was also able to detect which people with PD had rigidity or not, which correlated with traditional measures [32]. In addition, two concluded that their respective systems were able to differentiate the "on" and "off" states [31,32].…”
Section: Methods Using Sensors For the Capture And Analysis Of Movementmentioning
confidence: 88%
See 4 more Smart Citations
“…One of the sensors was also able to detect which people with PD had rigidity or not, which correlated with traditional measures [32]. In addition, two concluded that their respective systems were able to differentiate the "on" and "off" states [31,32].…”
Section: Methods Using Sensors For the Capture And Analysis Of Movementmentioning
confidence: 88%
“…Nine studies were included, which are summarized in Table 3. Of these, 5 examined the wrist [31][32][33][34][35], 2 examined the elbow [36,37], 1 examined the trunk [38], and 1 examined the entire body [39]. The evaluation protocol varied significantly between studies as the design and objectives were different.…”
Section: Methods Using Sensors For the Capture And Analysis Of Movementmentioning
confidence: 99%
See 3 more Smart Citations